2006
DOI: 10.1071/he06114
|View full text |Cite
|
Sign up to set email alerts
|

Health and well-being naturally: ‘contact with nature’ in health promotion for targeted individuals, communities and populations

Abstract: 'Contact with nature' constitutes a health promotion strategy with potential application in prevention, early intervention, treatment and care. Recommendations include further research to investigate the benefits of nature contact within existing interventions, and the impacts of 'active' and 'social' nature contact within tailored interventions for targeted individuals and communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Novel environments are thought to promote development when participants act to overcome challenge through mastery. Socioecological models have also connected naturebased adventure with healthy behavioral changes and eco-centric perspectives [66].…”
Section: The Environment Approachmentioning
confidence: 99%
“…Novel environments are thought to promote development when participants act to overcome challenge through mastery. Socioecological models have also connected naturebased adventure with healthy behavioral changes and eco-centric perspectives [66].…”
Section: The Environment Approachmentioning
confidence: 99%
“…The Victorian Health Promotion Foundation (2006; cited in Pryor et al 2006) has found that elderly people who are socially isolated have a greater likelihood of developing Alzheimer's disease, while other research has also shown that people of all ages who do not get sufficient social and emotional support, have a greater likelihood of experiencing depression . Numerous research studies have also cited evidence linking geriatric depression to the elderly population living in healthcare and long-term care settings (Smyer and Bartels 2002).…”
Section: Social Connectedness and Interactionsmentioning
confidence: 99%
“…Evidence from physiologically based studies has shown a positive effect of physical activity on body weight, body fat percentage, blood pressure, cholesterol ratios, triglyceride levels, glucose tolerance, insulin sensitivity and bone density (Bedimo-Rung et al 2005;Grahn and Stigsdotter 2003;Peacock et al 2007;Pryor et al 2006). Additionally, it has been shown to lower the risk of developing, as well as promote a better prognosis for, numerous chronic diseases such as cardiovascular disease, diabetes mellitus type 2, osteoporosis, stroke, depression and some forms of cancer (Bedimo-Rung et al 2005;Grahn and Stigsdotter 2003;Peacock et al 2007;Pryor et al 2006).…”
Section: Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations